Volatility of exchange rate and its impact on export growth Of textile sector of Pakistan - Ihsan, Dr. Hajra; Ghani, Abdul; Iqbal, Faisal (The journal of contemporary issues in business and government, 2022)
Exports being engine of an economy plays a vital role for the development of an economy. There are a number of factor that effect the exports of a country including exchange rate, domestic level of income, government policies of exports, production level of country, cost of raw materials and utilities. A number of studies have been done to investigate the relationship between the exchange rate and exports growth but there are no consensuses between them. According to some researcher there is positive relation between the exchange rate and export but some other disagree with them. This study is specially done to explain the relationship of exchange rate and export growth of textile sector of Pakistan and some other factor that influence the exports of textile products. For this purpose the whole textile sector of Pakistan is taken into study and we took the exports and exchange rate of last ten years from 2011 to 2020 as a sample for this study. Quantitative approach is used to analyze the impact of exchange rate on exports.